Children vagrancy: looking at the law and social impact in Malaysia / Amir Zharif Abdullah, Aqilah Suhaimi and Arnie Azlin Che Ariffin. - Abdullah, Amir Zharif; Suhaimi, Aqilah; Che Ariffin, Arnie Azlin (2007)
The topic of our research is Vagrants: Looking at the Law and Social Impact in Malaysia. Beggars have always existed in the world and they are also here in Malaysia. People result in begging as they have no other means or do not bother to seek other means to look for money. Beggars are always misunderstood and the law enforcers refuse to engage with this class of persons as they do not really commit any crimes. However, the lack of engagement leads to more problems and undetected crimes such as human trafficking. This.is something that could be avoided if all parties to the issue play a part. The topic seeks to venture into the problem of beggars that is advent in Malaysia where there is clear evidence that this problem has not been tackled. We believe that the law could be better in terms of dealing with this group of persons as they are also citizens of our country. Even if they are not, at least the current law must be enforced properly to ensure that the problem faced by beggars and the society could be reduced.